Dye sensitized solar cells based on double-layered titanium dioxide and their evaluation in tropical hot desert climate of Saudi Arabia. (September 2019) - Babkair, Saeed Salem; Alzubaydi, Reem Ali; Ansari, Azhar Ahmad; Al-Hadeethi, Yas
Abstract: Dye-sensitized solar cells (DSSCs) based on double layered photo-anode geometry incorporating transmitting and absorbing layers of titanium dioxide which are activated with a known stable C106 dye have been fabricated. The photovoltaic parameters have been studied both indoors under standard reporting conditions (AM 1.5G at 100 mW/cm 2 irradiation) as well as under the actual harsh outdoor conditions in Jeddah, Saudi Arabia, one day each month for a full one year period. Outdoor performance of cell exhibited the power conversion efficiencies of over 9% with a small degradation over a one year period. Reasons for degradation in the performance of cell parameters have been discussed in the text. Highlights: DSSCs with efficiencies of about 9% have been fabricated. Cell performance for one year is studied under outdoor operating conditions. These are the first reported results for Jeddah in real operating conditions. DSSCs are less sensitive to temperatures and more suitable for desert climes. Geographical location of Jeddah is ideal to yield high output throughout the year.